Performance Improvement of Sand-Based Batteries using Sea Sand and Metal Waste as an Alternative Energy Storage System - Siswanto; Rusdianasari; Indrayani (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
The shift to renewable energy faces the challenge of intermittency, which requires effective Energy Storage Systems (ESS). Sand-Based Thermal Energy Storage (TES) presents a cost-effective and environmentally friendly solution, although it suffers from the low thermal conductivity of sand. This research seeks to enhance the thermal efficacy of sand batteries by incorporating waste iron shavings from lathes as a composite material and examining its suitability for pilot-plant scale heating.A 96-liter sand battery container was used with varying mixtures of iron waste at 0%, 10%, 20%, and 30% relative to the volume of sea sand. The charging process used a 4000-watt power supply for simulation and 4000 Wp solar panels for validation. The discharge process was implemented to provide heat to a copra drying oven. The findings indicate that incorporating waste iron significantly improves the heat transfer rate and temperature uniformity during charging. The composition with 30% iron (P-30) demonstrated the most favorable thermal properties. During discharge tests, the system maintained the copra drying oven temperature within 56-57°C for over 12 hours, meeting the required drying temperature standards. This study proves that sand batteries with a waste iron composite represent an effective, cost-effective, and sustainable TES solution for thermal applications in the context of renewable energy.